MYSTIC WISDOMS IN POETRY - Jummaevna , Gulandom Togaeva (Journal of Higher Education and Academic Advancement, 2024)
Taking advantage of Islamic enlightenment, Sufi poetry is filled with the wisdom of the Quran and Hadith, the essence of Islam, and encourages the transformation of hearts with the passion of the world of love. This article talks about the mystical aspects of Mirzo Kenjabek’s poetry, his quest to create a poetic image.